Associations of Daily Pedometer Steps and Self-Reported Physical Activity With Health-Related Quality of Life: Results From the Alberta Older Adult Health Survey. (June 2016) - Vallance, Jeff; Eurich, Dean; Gardiner, Paul; Taylor, Lorian; Johnson, Steven
Objective: The aim of this article is to examine associations of self-reported physical activity (PA) and pedometer steps with health-related quality of life (HRQoL) among a population-based sample of older adults.Method: Adults ≥55 years ( N = 1, 296) were recruited through random-digit dialing and responded to a questionnaire via computer-assisted telephone interviewing methods. Questionnaires assessed demographic variables and validated measures of PA and HRQoL. Participants received a step pedometer and waist circumference tape measure via post.Results: Compared with participants in the low-step group (0-6, 999 steps/day), participants in the high-step group (>10, 000 steps/day) had significantly higher scores on mental health ( M diff = 3.1, p < .001, confidence intervals [CI] = [1.8, 4.3]), physical health ( M diff = 3.5, p < .001, CI = [2.2, 4.7]), and global health ( M diff = 3.5, p < .001, CI = [2.3, 4.7]). Waist circumference and body mass index did not moderate any associations of pedometer steps and PA with HRQoL.Conclusion: Older adults exceeding established step thresholds reported significantly higher HRQoL indices compared with those achieving lower thresholds.